PTPTN wipes out national hero's loan debt - Borneo Post, (KK) (Borneo Post (KK), 2013)
KANGAR: The National Higher Education Fund Corporation (PTPTN) has wiped out the studyloan debt of national hero, ASP Zulkifli Mamat, who was killed while defending the country's sovereignty in Lahad Datu, Sabah last month.